Relationship of Cholinesterase with Erythrocyte Index of Female Farmers in Vegetable Farming Area - Silvia, Silvia; Yuniarti, Elsa; Syah, Nurhasan; Azzahra, Nabila (Jurnal Kebidanan Midwiferia, 2025)
Reproductive and maternal health in female farmers, especially those exposed to pesticides, is an urgent issue in Indonesia. Pesticide exposure during agricultural activities can cause disorders in the reproductive system, pregnancy, and fetal development. This study aims to analyze the relationship between cholinesterase levels (an indicator of pesticide exposure) and erythrocyte indices (including Hb, MCV, MCH, and MCHC) in female farmers working in vegetable farming areas in Agam Regency, West Sumatra. A total of 33 female farmers divided into two groups, namely the pesticide-exposed group (17 people) and the control group (16 people), were used as research samples. The results showed that the group exposed to pesticides had lower cholinesterase levels than the control group, with a significant difference. In addition, there was a significant relationship between decreased cholinesterase levels and decreased MCHC and increased risk of anemia in the exposed group. This decrease in cholinesterase indicates the adverse effects of pesticide exposure on the hematological system, which has the potential to cause complications in reproductive health such as menstrual disorders, infertility, and pregnancy complications. Therefore, this study provides important evidence regarding the need for better health screening for female farmers in agricultural areas. Routine monitoring of cholinesterase levels and erythrocyte indices can be an effective preventive measure in protecting the reproductive and maternal health of women working in the agricultural sector.